2008
DOI: 10.1039/b714667a
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of Mg(ii) and Nα-4-tosyl-l-arginine methyl ester hydrochloride on the recognition and catalysis in ATP hydrolysis

Abstract: The supramolecular interactions of Mg(ii) and N(alpha)-4-tosyl-l-arginine methyl ester hydrochloride (TAME) with ATP have been investigated using (1)H and (31)P NMR spectra. Furthermore, the hydrolysis of ATP catalyzed by Mg(ii) and TAME has been studied at 60 degrees C and pH 7 using (31)P NMR spectra. In the Mg(ii)-ATP-TAME ternary system, the binding interaction of Mg(2+) with ATP involves not only N1 and N7 in the adenine ring but also beta- and gamma-phosphate of ATP. The binding forces are mainly electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
2
3
0
Order By: Relevance
“…The 31 P spectra show an overall generalized broadening upon metal ion addition. However, despite the strong overlap, a few peaks could be followed during to the β, γ-phosphates and N7 of G1 TP [35,36]. The same behaviour was recently observed in the case of D1κζ [12].…”
Section: Cd(ii) Titration Performed In Kclo 4 : 2 J-[ 1 H 15 N]-hsqcsupporting
confidence: 74%
“…The 31 P spectra show an overall generalized broadening upon metal ion addition. However, despite the strong overlap, a few peaks could be followed during to the β, γ-phosphates and N7 of G1 TP [35,36]. The same behaviour was recently observed in the case of D1κζ [12].…”
Section: Cd(ii) Titration Performed In Kclo 4 : 2 J-[ 1 H 15 N]-hsqcsupporting
confidence: 74%
“…2 provide information about the interaction between the phosphate chain and the different metal ions. All experimental data of metal-ATP are similar to the Mg 2+ -ATP binary system analyzed in the previous work in detail 23 . All the conclusions outlined for Mg 2+ -ATP are also valid for Ca 2+ -ATP, Cd 2+ -ATP and Zn 2+ -ATP binary systems.…”
Section: Resultssupporting
confidence: 57%
“…This indicates that the interaction between TAME and phosphate chain is relative weaker than the interaction between metal ions and phosphate chain 30 . Metal-ATP binary system: Mg 2+ complexation study previously performed on the binary adenosine triphosphate system indicated the formation of a 1:1 complex 23 . Analogous techniques were used in this study to determine binary and ternary systems complexation tendencies, i.e., by monitoring 1 H and 31 P chemical shifts with the different metal ions.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations